2019
DOI: 10.1007/s00709-019-01345-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple non-toxic ethylene carbonate fluorescence in situ hybridization (EC-FISH) for simultaneous detection of repetitive DNA sequences and fluorescent bands in plants

Abstract: The major drawbacks of standard plant fluorescence in situ hybridization (FISH) designed for double-stranded DNA probes include requirement for experimentally determined heat denaturation of chromosomes at high temperatures and at least overnight hybridization. Consequently, processing with chromosomal preparations may easily result in heat-induced deterioration of chromosomal structural details, is time-consuming, and involves the use of toxic formamide and formaldehyde. Here, I have described a simple and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Cuadrado et al (2009) showed that, regardless of whether hybridization lasted overnight, 2 h, 1 h, or 30 min, they were able to obtain clear hybridization signals. Based on literature data (Matthiesen and Hansen, 2012;Golczyk, 2019) and the results of our work, it seems that the hybridization time may also be reduced in the case of EC-FISH.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Cuadrado et al (2009) showed that, regardless of whether hybridization lasted overnight, 2 h, 1 h, or 30 min, they were able to obtain clear hybridization signals. Based on literature data (Matthiesen and Hansen, 2012;Golczyk, 2019) and the results of our work, it seems that the hybridization time may also be reduced in the case of EC-FISH.…”
Section: Resultssupporting
confidence: 61%
“…In this study, ND-FISH (non-denaturing fluorescence in situ hybridization) was not tested, because denaturation at 83 °C does not affect chromosome morphology. Golczyk (2019) obtained satisfactory results after hybridization for 3 h. The use of JNK and Bilby probes allowed to obtain positive hybridization results after 90 min of its duration. Thus, it seems that EC-FISH does not only enable avoidance of toxic compounds, but it may also be a time-saving procedure.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Hybridization protocols require the use of the toxic solvent formamide for the reliable annealing of oligonucleotide probes to the target site, and studies are being conducted to replace formamide with non-toxic substances and still to achieve reliable annealing of the probes to the target sequence. Matthiesen and Hansen [ 203 ] revealed promising results using ethylene carbonate in non-toxic concentrations instead of formamide for tissue FISH, whereas Kalinka, My, and Achrem [ 204 ] and Golczyk [ 205 ] successfully substituted formamide with ethylene carbonate in plant FISH. Urea was used as a formamide alternative for the detection of gene expression in diverse animal species [ 206 ].…”
Section: Strategies To Overcome Limitations and To Improve Detection Methodsmentioning
confidence: 99%